Improvement of Fatigue Properties of AZ31B Extruded Magnesium Alloy through Forging (Fracture and Structural Integrity, 2020)
Axial monotonic and load-controlled fatigue tests were performed to investigate the influence of forging at various temperatures and different deformation rates, on both the microstructural and mechanical behaviour of extruded AZ31B magnesium alloy. The obtained microstructural analysis showed that the extruded AZ31B magnesium alloy possesses a bimodal grain structure with strong basal texture. In contrast, once forged, the material showed refined grains and a modified texture. A monotonic yield and ultimate tensile strength of about 223 MPa and 278 MPa were observed for the forged samples showing an increase of 18%, from the as-extruded material. The optimum forging condition was determined to be the coldest of the investigated temperatures, based on the improvement in both monotonic and cyclic properties vs. the as-extruded material. The fractographic analysis of the failure surfaces showed that ductile type fractures occurred in both as-extruded and forged samples. However, more dimples and plastic deformation were identified in the fracture surfaces of the forged specimens. A significant improvement of fatigue life was also observed for all of the forged samples, in particular those forged at 400°C and 39 mm/min. Forging improved the fatigue life via a combination of grain refinement and texture modification resulting in improved strength and ductility.
Keywords: Magnesium; Forging; Fatigue Characterization; Texture; AZ31B